ANALISIS FILM SANG PEMIMPI DALAM PENANAMAN NILAI DAN MORAL SISWA (JS (JURNAL SEKOLAH), 2023)
Abstract : The purpose of this research is to analyze the film The Dreamer in inculcating students' values and morals. The research subjects were grade 5 students at SD Negeri 064027 Medan Polonia. The method in this study uses descriptive research with a qualitative approach. Data collection techniques using questionnaires and interviews. The results of the study can be concluded that the film Sang Pemimpi is effective in instilling students' values and morals. This is evidenced by an increase in students' understanding of values and morals after watching films and participating in discussions. In addition, films also influence students to appreciate diversity, hard work, simplicity, and honesty. The film Sang Pemimpi also succeeded in attracting students' attention with an interesting and entertaining story. This makes it easier for students to understand the moral message conveyed in the film. In the discussion after watching the film, students showed high enthusiasm and were able to analyze the values and morals contained in the film.Keyword : Film Sang Pemimpi, Values and MoralsAbstrak: Tujuan penelitian ini untuk menganalisis film sang pemimpi dalam penanaman nilai dan moral siswa. Subjek penelitian yaitu siswa kelas 5 SD Negeri 064027 Medan Polonia. Metode pada penelitian ini menggunakan penelitian deksriftif dengan pendekatan kualitatif. Teknik pengumpulan data dengan menggunakan kuesioner dan wawancara. Hasil penelitian dapat disimpulkan bahwa film Sang Pemimpi efektif dalam penanaman nilai dan moral siswa. Hal ini dibuktikan dengan peningkatan pemahaman siswa mengenai nilai dan moral setelah menonton film dan mengikuti diskusi. Selain itu, film juga mempengaruhi siswa untuk lebih menghargai keberagaman, kerja keras, kesederhanaan, dan kejujuran. Film Sang Pemimpi juga berhasil menarik perhatian siswa dengan cerita yang menarik dan menghibur. Hal ini membuat siswa lebih mudah untuk memahami pesan moral yang disampaikan dalam film. Dalam diskusi setelah menonton film, siswa menunjukkan antusiasme yang tinggi dan mampu menganalisis nilai dan moral yang terkandung dalam film.Kata Kunci: Film Sang Pemimpi, Nilai dan Moral